Implementation strategies – moving guidance into practice. (11th January 2013) - Latibeaudiere, Monique; Phillips, Justin; Siassakos, Dimitrios; Winter, Cathy; Draycott, Tim; Fox, Robert
<x xml:space="preserve">Abstract</x> Key content The importance of guideline development. The gap between knowledge and practice. Evidence for implementation strategies. Learning objectives To understand how simple guidelines fail to promote change. To understand the evidence for implementation tools. To understand the range of implementation tools, such as: integrated care pathways, care bundles (venous thromboembolism [VTE] risk assessment), equipment boxes (e.g. eclampsia), decision stickers (e.g. cardiotocography [CTG] analysis), safety briefings/structured ward rounds. How to go about designing an implementation project. How to effect change.